The Role of Eco Supply Chain on Environment and Operational Performance of Indonesian Defense Industry - Permana , Ade Indra; Soediantono, Dwi (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this study is to analyze the relationship between Eco supply chain management and operational performance, the relationship between Eco supply chain and environmental performance, and the relationship between environmental performance and operational performance. This research is quantitative with survey technique as a data collection tool. The sampling technique was proportional random sampling using an online questionnaire as a data collection tool with 250 staff of industry managers as respondentsThe data analysis technique uses Partial Least Square with SmartPLS 3.3.3 software tools. Based on the analysis concluded that Eco supply chain management has a positive effect on operational performance, Eco supply chain has a positive effect on environmental performance, Environmental performance has a positive effect on operational performance, environmental performance mediates the effect of eco supply chain on operational performance.